Relationship between Employee Development and Work Motivation of Solider Rural Bank Employees - Rusmia Maria Situmorang (Enrichment : Journal of Management, 2019)
Solider Rural Credit Bank is a company engaged in people's credit (savings / loans). Employee development with efforts to improve skills and general knowledge for Solider Rural Credit Bank employees is a part that encourages them to work harder in the future with the desire to prepare themselves for new positions. Based on preliminary research that has been done, the problems faced by the company are as follows: "Is there a relationship between employee development and employee work motivation?". The hypothesis put forward in connection with the problem is: "employee development is related to employee work motivation". Data analysis method used by two methods, namely: Descriptive method; namely collecting, classifying and interpreting data according to the actual and Deductive Method; is a drawing of special conclusions based on theories that are accepted as general truths about observed facts. From the results of the analysis and evaluation the following conclusions are obtained: 1. The development of the Solider Rural Bank Bank employees has made employees able to develop themselves in such a way. This means that a lot of employee development that is followed by employees or carried out by the company is more general in nature than specific or specified. 2. There is a significant relationship between employee development with employee motivation at the Solider Rural Credit Bank. This means that increasing the quality of the implementation of employee work development in the company will increase work motivation. From this study it can also be concluded that this is a dominant factor affecting employee work motivation.